(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Holostemma annulare is a twining perennial shrub belonging to the family Asclepiadaceae with therapeutic and pharmacological potentialities. The root tuber of the plant is rich in antioxidants and have been suggested as potential sources of anti-inflammatory compounds. Thus the antioxidant and anti- inflammatory activities of the methanolic in vivo and in vitro root tuber extracts of the H. annulare with wide spread use in folk medicine were evaluated in this study. Antioxidant activity was evaluated by DPPH, Nitric oxide, Hydrogen peroxide, Superoxide scavenging and Reducing power activity assays. In addition, in vitro anti-inflammatory activity of the methanol root tuber extracts was evaluated by proteinase inhibition assay, COX and LOX assays. The results revealed that in vitro root tuber extracts possesses significant antioxidant and anti- inflammatory activities to the extent of in vivo tubers and thus can be explored as an important sources of novel antioxidant and anti- inflammatory agents. This application also emphasizes the potential utilization of in vitro tubers of the species for drug formulations.